If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1y(2x + 1) = 3 Reorder the terms: 2x + -1y(1 + 2x) = 3 2x + (1 * -1y + 2x * -1y) = 3 Reorder the terms: 2x + (-2xy + -1y) = 3 2x + (-2xy + -1y) = 3 Solving 2x + -2xy + -1y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 2x + -2xy + -1y + y = 3 + y Combine like terms: -1y + y = 0 2x + -2xy + 0 = 3 + y 2x + -2xy = 3 + y Reorder the terms: -3 + 2x + -2xy + -1y = 3 + y + -3 + -1y Reorder the terms: -3 + 2x + -2xy + -1y = 3 + -3 + y + -1y Combine like terms: 3 + -3 = 0 -3 + 2x + -2xy + -1y = 0 + y + -1y -3 + 2x + -2xy + -1y = y + -1y Combine like terms: y + -1y = 0 -3 + 2x + -2xy + -1y = 0 The solution to this equation could not be determined.
| -2x-107=133+6x | | (4-9i)(7-9i)= | | 14k+13=20 | | 4(c-2)=3(x-3) | | 4k+13=13 | | -133-2x=119-11x | | 7(m-4)=-29+7m | | z=(6+x)k | | -8(y+4)=6-7y | | n-20=n*6+15 | | 2x(2x+1)=3 | | mn-2n+7m-14= | | 3x-6=2x+17 | | 81x-100y^4=0 | | 24x^2-8x^2= | | 7(x+3)+5=-6(x-1) | | -(8x-3)-(3x-5)+11=-9(x-1)-(7x+8)+3 | | 8+4y=4 | | -2(4-3x)6x=10 | | 6(x-7)+6=3(x-6) | | 3x-17=5+2x | | -6(5-x)+1=3(x+2) | | 11x-3=5x+21 | | 0.16-0.01(x+2)=0.03(2-x) | | 4(n-12)=12(n-4) | | 125+m=725 | | 35=-2x-25 | | 4(n-12)=12(4-n) | | -4/5=-1/4-5/6q | | (9x-4)(5x+5)= | | X^2-8=9x | | -7(-4-4x)-6=1+7x |